Moderating effect of gender and marital status in the association between religiosity and happiness among Bangladeshi university students - Md. Abdul Hannan Mondal; Md. Burhan Uddin Zubair; Pramath Chandra Sarker; Md. Nur-E-Alam Siddique; Md. Golam Hossain (Acta Psychologica)
Background: Boosting university students' happiness is essential for personal development, familial harmony, social equilibrium, and national progress. The present study aimed to determine the significant influential factors of happiness, as well as whether gender and marital status have a moderating effect on the relationship between religiosity and happiness among Bangladeshi university students. Methods: A total of 464 students were recruited for the present study, they were selected by multistage random sampling. Bangla-adapted version of the MUNSH scale was used to measure the happiness of university students. We asked a question to respondents for measuring the religiosity, “Do you practice your religion?” (Yes, considered as higher religious, and No, considered as lower religious or no). T-test and correlation analysis were used to analyze the data. The PROCESS macro (Model 1) was applied to see the moderating effect of gender and marital status. Results: Among 464 participants, 48.30 % and 51.70 % were males and females, respectively. The mean age of the students was 21.07 ± 2.60 years. Firstly, we found that gender, marital status, and religiosity significantly influenced the happiness of university students. Secondly, the correlation analysis revealed that relationship between religiosity and happiness was positively significant. Thirdly, the results also revealed that the moderating effect of gender between religiosity and happiness was negative but not significant (β = −0.65, p > 0.05, 95 % CI = [−3.23, 1.94]). Fourthly, the moderation analysis showed that marital status was the positive and significant moderator in the association between religiosity and happiness (β = 5.17, p < 0.01, 95 % CI = [2.05, 8.28]). Finally, the selected model of moderation could able to explain the variation of happiness by 38.92 %. Conclusions: This study suggests that happiness depends on changes in many socio-demographic variables, such as gender, marital status, and religiosity. Marital individuals show a higher moderating effect than unmarried individuals in the association between religiosity and happiness. Both health authorities and university authorities may consider the findings to address the problem faced by university students.